Analysis of the Influence of Current Ratio, Debt to Total Assets, Debt to Equity Ratio, Return on Assets, and Return on Equity on Stock Prices - Intan Permata Sari; Mahameru Rosy Rochmatullah (International Journal of Economics Development Research (IJEDR), 2023)
The aim of this research is to analyze the influence of Current Ratio, Debt to Total Assets, Debt to Equity Ratio, Return on Assets, and Return on Equity on Stock Prices in food and beverage companies listed on the Indonesia Stock Exchange during the period 2019-2022. This study utilizes secondary data with a population comprising 43 food and beverage companies listed on the Indonesia Stock Exchange for the observation years 2019-2022. The technique employed is purposive sampling with multiple linear regression analysis method. The results of this study indicate that, partially, Current Ratio, Debt to Total Assets, Debt to Equity Ratio, and Return on Assets do not significantly influence Stock Prices in food and beverage companies listed on the Indonesia Stock Exchange during the years 2019-2022. However, Return on Equity significantly influences the stock prices of food and beverage companies listed on the Indonesia Stock Exchange during the years 2019-2022.